(untitled) (Research, Society and Development, 2021)
Osteoporosis is characterized by loss of bone mass and deterioration of bone tissue microarchitecture and, consequently, bone fragility. The bone affected by this disease can be found in the maxilla and mandible, influencing several dental procedures. In this context, the assessment of bone wear using radiological resources to investigate bone density and mineral content is essential. This work aims to carry out a literature review on the relationship between osteoporosis and its impacts on oral health. For the operationalization of the review, the following descriptors were used: osteoporosis, oral health and elderly with the Boolean operator AND, according to the databases: BVS, LILACS, SciELO and PubMed. There is a shortage of finding papers that address the topic, which demonstrates the need for further studies on the subject. Therefore, nineteen articles were selected for the preparation of the review. It is concluded that it is necessary to identify the factors that predispose to an increased risk (menopausal women, vitamin D deficiency, osteoporotic elderly and diabetes mellitus) in order to act preventively in order to obtain positive clinical outcomes. Therefore, it is extremely necessary to carry out studies to identify greater relationships between Osteoporosis and Osteopenia with changes in the Oral cavity and their clinical repercussions.